Asian Philosophies and Authoritarian Press Practice: A Remarkable Contradiction - Gunaratne, Shelton A. (Javnost-The Public, 2005)
Contrary to Orientalist interpretations, authoritarian political practices are inconsistent with the axial Asian philosophies, which implicitly call for a socially responsible critical press (communication outlets). This is certainly the case with Buddhist philosophy. Confucianism and Hinduism also do not endorse authoritarianism. First, this essay analyzes each of these philosophies to show their disapproval of actions that enhance state authority and central control against people’s wellbeing. Second, it identifies the probable reasons for the discrepancy between the ethico-political orientations of the main Asian philosophies and the authoritarian press practice prevalent in much of Asia and elsewhere, namely, (a) the failure of the Westcentric modernisation paradigm to uplift the .sovereign nation-states. in the periphery of the modern world-system, which grew out of the erstwhile colonial empires; (b) the appeal of continuing with the colonial tradition of governing through coercive and autocratic institutions to suppress public criticism; and (c) the impact of Orientalism, which caused the rulers of the new .nation-states. to misconstrue or ignore the principles embodied in Asian philosophies. Thus, political-economic reality appears to have superseded the ethico-political orientations of Asian philosophies in engendering the putative Asian model of development. However, because concepts such as freedom, democracy, authoritarianism, and social responsibility evoke different connotations in the West and the East, Freedom House’s ranking of countries based on Westcentric criteria is debatable.